Geographic variation in the probability of being born with and retaining contrasting tail tip colour (tail luring) in the Common Lancehead Bothrops jararaca - Siqueira, Lucas Henrique Carvalho [UNESP]; Piantoni, Carla; Marques, Otavio Augusto Vuolo [UNESP] (Canadian Science Publishing, 2024)
In snakes that are known to be ambush predators, tail luring, in which the movement of a snake’s tail resembles that of a worm or insect larva and is used to attract prey, has emerged as a complementary hunting strategy. In certain species, some individuals may present a conspicuously bright colour at the tail tip, which eventually disappears with age. Some au-thors argue that the bright colour enhances the resemblance of the snake’s tail with a potential food item, increasing the success of capture. Here, we tested the influence of geographic variation, sex, and environmental factors on the probability that Common Lanceheads Bothrops jararaca (Wied-Neuwied, 1824) from southeastern Brazil were born with this contrasting tail tip and whether snakes retain this trait throughout adulthood. None of the predictors affected the probability of births with a contrasting tail tip. However, a higher proportion of individuals from the coastal populations retained this trait into adulthood. The absence of difference in the probability of being born with this trait indicates that there are other factors influencing tail tip colour, such as phylogenetic correlates, rather than intrinsic or environmental factors. A higher proportion of ectothermic prey in the diet of coastal populations may explain why this population retains tail luring throughout adulthood.
Keywords: aggressive mimicry; Bothrops jararaca (Wied-Neuwied, 1824); caudal luring; feeding; pit viper; population ecology